Development of a tool to improve performance debriefing and learning: the paediatric Objective Structured Assessment of Debriefing (OSAD) tool. Issue 1069 (8th September 2014) - Runnacles, Jane; Thomas, Libby; Sevdalis, Nick; Kneebone, Roger; Arora, Sonal; Cooper, Mehrengise
Abstract: Background: Simulation is an important educational tool to improve medical training and patient safety. Debriefing after simulation is crucial to maximise learning and to translate the lessons learnt to improve real clinical performance, and thus to reduce medical error. Currently there are few tools to improve performance debriefing and learning after simulations of serious paediatric situations. Purpose: The purpose of this study was to develop a tool to guide and assess debriefings after simulations of serious paediatric situations, applying the current evidence base and user-based research. Study design: A literature review and semistructured interviews (performed in 2010) to identify important features of a paediatric simulation debriefing. Emergent theme analysis was used to identify key components of an effective debriefing which could be used as a tool for assessing debriefing effectiveness. Results: The literature review identified 34 relevant studies. Interviews were carried out with 16 paediatricians, both debriefing facilitators and learners. In total, 307 features of a debriefing were identified. These were grouped into eight dimensions representing the key components of a paediatric debriefing: the facilitator's approach, learning environment, engagement of learners, reaction, descriptive reflection, analysis, diagnosis and application. These eight dimensions were used to create a tool, the Objective Structured Assessment of Debriefing (OSAD). Each dimension can be scored on a five-point Likert scale containing descriptions for scores 1, 3 and 5 to serve as anchors and aid scoring. Conclusions: The study identified the important features of a paediatric simulation debriefing, which were developed into the OSAD tool. OSAD offers a structured approach to paediatric simulation debriefing, and is based on evidence from published literature and views of simulation facilitators and learners. OSAD may be used as a guide or assessment tool to improve the quality of debriefing after paediatric simulation.